2018
DOI: 10.3390/genes10010014
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Replication Template-Switching by DNA-Protein Crosslinks

Abstract: Covalent DNA protein crosslinks (DPCs) are common lesions that block replication. We examine here the consequence of DPCs on mutagenesis involving replicational template-switch reactions in Escherichia coli. 5-Azacytidine (5-azaC) is a potent mutagen for template-switching. This effect is dependent on DNA cytosine methylase (Dcm), implicating the Dcm-DNA covalent complex trapped by 5-azaC as the initiator for mutagenesis. The leading strand of replication is more mutable than the lagging strand, which can be e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…A second model is that the replication machinery stalls at lesions such as pyrimidine dimers and will skip ahead, leaving a gap of ssDNA that provides a suitable substrate for RecA binding (54). A primer generated from an RNA transcript (55) or by primase (56) can allow DNA polymerase to advance beyond a DNA lesion on the leading strand, or this can occur through template switching (57,58). The resulting ssDNA gap generated by DNA polymerase skipping ahead on the leading strand can be used as the substrate for loading RecA by the RecFOR complex (59).…”
mentioning
confidence: 99%
“…A second model is that the replication machinery stalls at lesions such as pyrimidine dimers and will skip ahead, leaving a gap of ssDNA that provides a suitable substrate for RecA binding (54). A primer generated from an RNA transcript (55) or by primase (56) can allow DNA polymerase to advance beyond a DNA lesion on the leading strand, or this can occur through template switching (57,58). The resulting ssDNA gap generated by DNA polymerase skipping ahead on the leading strand can be used as the substrate for loading RecA by the RecFOR complex (59).…”
mentioning
confidence: 99%
“…We use distilled water as a negative control and 100 mg/mL (409.5 mM) 5-azaC as a positive control. This concentration of 5-azaC was chosen since it has been shown to induce QPM with the disk diffusion assay (Laranjo et al 2018). If a compound stimulates template switching, after one or two days, a blue halo around the filter disk containing the compound will appear.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that template-switch associated mutations are a significant subset of mutational events that have not been thoroughly investigated, in this study, we tested the effect of drugs on their ability to promote template-switch events. Our previous work has shown that azidothymidine (zidovudine, AZT) and other antiviral chainterminators, as well as drugs known to stall replication through the formation of DNA-protein crosslinks (DPCs), such as 5-azacytidine (5-azaC), stimulate QPM (Seier et al 2012;Laranjo et al 2018). To discover more mutagens for template-switch events, we designed a disk diffusion test for screening small molecule libraries.…”
mentioning
confidence: 99%
“…While we have shown that PrimPol re-priming initiates HR at UV, 4-NQO and BPDE DNA adducts, it will be interesting to investigate whether other bulky lesions or replication impediments can be channelled into this pathway. DNA-protein crosslinks for example engage HR for repair 41, 42 and lead to templateswitching 43 raising the question whether PrimPol could act at these lesions as well. PrimPol also re-primes at R-loops and secondary structure-forming sequences 44, 45 , opening up the possibility that HR in those backgrounds might depend at least partially on PrimPol.…”
Section: Discussionmentioning
confidence: 99%